2004
DOI: 10.1002/ijc.20236
|View full text |Cite
|
Sign up to set email alerts
|

Interferon receptor expression regulates the antiproliferative effects of interferons on cancer cells and solid tumors

Abstract: In addition to antiviral effects, Type I interferons (IFN) have potent antiproliferative and immunomodulatory activities. Because of these properties IFNs have been evaluated as therapeutics for the treatment of a number of human diseases, including cancer. Currently, IFNs have been shown to be efficacious for the treatment of only a select number of cancers. The reason for this is unclear. Recent evidence has demonstrated that some cancer cell types seem to be defective in their ability to respond to IFN. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 54 publications
1
48
0
1
Order By: Relevance
“…Of course, for a drug against a disease such as cancer, an increased antiproliferative activity of IFN would be desired. Our data suggest that by further increasing the affinity of IFN for IFNAR1, such an increased activity could be achieved, even in cancer cells that have lost their responsiveness to IFNs by receptor down-regulation (49).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Of course, for a drug against a disease such as cancer, an increased antiproliferative activity of IFN would be desired. Our data suggest that by further increasing the affinity of IFN for IFNAR1, such an increased activity could be achieved, even in cancer cells that have lost their responsiveness to IFNs by receptor down-regulation (49).…”
Section: Discussionmentioning
confidence: 81%
“…In Daudi cells, low concentrations of IFNs (pM) already cause growth arrest, which may be linked to higher levels of the interferon receptors on the surfaces of Daudi cells than on WISH cells (6). A recent report has suggested that tumor cells have a reduced level of interferon receptors, making them resistant to the antiproliferative activity of IFNs (49). Thus, it seems that interferon receptor concentrations affect the biological activities of IFNs.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were stained with hematoxylin-eosin (H&E) for histological analysis. The protocol closely followed that used successfully by Wagner et al (27).…”
Section: Determination Of Icmentioning
confidence: 98%
“…It was shown that a decrease in cell surface concentration of one or both of the receptor subunits reduces cell sensitivity and alters signaling (5,25,26,43,49). In addition, a clear correlation between the efficiency of interferon as an antiviral drug or a cancer drug and surface receptor concentration was suggested (7,12,27,49). Using stably transfected cells, it was shown that an increased number of receptors resulted in an overall elevated sensitivity for IFNs, accompanied by a de-crease in interferon differential activity between the low-and high-affinity cytokines IFN-␣ and -␤ (29).…”
mentioning
confidence: 99%